Enantioselective Addition of Dimethylzinc to Aldehydes Catalyzed by a Chiral Perhydro-1,3-benzoxazine-Based Amino Alcohol as Ligand - Infante, Rebeca; Nieto, Javier; Andrés, Celia (Synthesis, 2012)
Dimethylzinc undergoes efficient enantioselective addition to a wide variety of aromatic and aliphatic aldehydes in the presence of a catalytic amount of a chiral perhydro-1,3-benzoxazine-based amino alcohol. Methyl carbinols are obtained in good yields and in enantiomeric excesses of 99% or more in the absence of any metal other than zinc.
Keywords: asymmetric catalysis; zinc; aldehydes; chiral auxiliaries; amino alcohols